The Effectiveness of Ischemia Modified Albumin in Determining Acute Cholecystitis and its Severity - Gul, Evrim; Gul, Yeliz; Ozkan, Zeynep; Kalayci, Mehmet; Gurger, Mehtap; Atescelik, Metin; Ucarel, Mustafa (Clin Lab Publ, 2021)
Background: Acute cholecystitis (AC) is caused by chemical and bacterial inflammation of the gallbladder. The use of Tokyo guidelines is recommended in determining the diagnosis of AC and its clinical severity. In the early stages of AC, many cytokines are secreted due to the local inflammatory cell activation, leading to exacerbation of inflammation and organ failure. Ischemia modified albumin (IMA) is a type of albumin that occurs in ischemia and oxidation and is used as a marker of hypoperfusion and oxidative stress. This study aims to investigate the ef-fectiveness of ischemia modified albumin, C-reactive protein (CRP), and some other inflammation parameters in predicting the severity of the AC on admittance. Methods: Forty-two patients diagnosed with AC and 30 healthy individuals in the control group were included in the study. The severity assessment of the patients was performed based on the revised Tokyo guidelines (TG 13). The patients were divided into 3 groups according to severity of the disease. Blood samples were taken from the subjects on admittance. Serum IMA levels were studied using an ELISA kit. SPSS 22.00 package program was used for statistical analysis. Results: Thirty (71.4%) of the participants were in the mild group, while 12 (28.6%) were in the moderate group. There were no patients in the severe group. Leukocyte, CRP, and IMA values in the patient group were higher than those of the control group (p > 0.05). According to the Tokyo classification, a significant difference was found between the groups with mild and moderate grades in terms of CRP and IMA values (p < 0.001 and p < 0.05, re-spectively). When the cutoff value of IMA was 84 ng/mL, the sensitivity was found to be 76% and specificity was determined to be 40% (AUC: 0.665, p = 0.017, 95% Confidence Interval). Conclusions: It is considered that IMA could be useful in predicting the clinical severity of TG13-based acute cho-lecystitis and, therefore, could be used in the management of treatment by the clinician such as medical treatment, early surgery, and interval surgery. (Clin. Lab. 2021;67:2071-2078. DOI: 10.7754/Clin.Lab.2021.210116)
Keywords: acute cholecystitis; revised Tokyo guidelines; ischemia modified albumin; C-reactive protein